Educar mentes e salvar almas : ação missionária protestante na escolarização de indígenas no sul do Mato Grosso (1928-1950) - Paes, Fernando Luís Oliveira Athayde (Universidade Federal de São Carlos, 2015)
This research is linked to the line "History, Philosophy and Sociology of Education" from the Doctoral degree in Education, Post-Graduation Program in Education (PPGE) in the Federal University of São Carlos (UFSCar).The work aimed to search the Protestant missionary action in the schooling of Guarani Kaiowá indigenous ethnic group schooling in Evangelical Mission Caiuá in the south of Mato Grosso. The work aimed to search the protestant missionary activity in the schooling of indigenous from the ethnic group Guarani-Kaiowá in the Evangelical Caiua Mission in the old south of Mato Grosso. It was chosen as chronological temporal cut, the initial period understood as the arrival time of the first Protestant missionaries to that region (1928), culminating with the migrations that were consolidated during the 1950s, through the Agricultural Colony of Dourados (CAND ) and the admission of respondents in the Mission. The theoretical - methodological support, to provide subsidies to the collection, analysis and text editing, counted on contributions from the history and researchers who dedicated to the topic in the field of Mato Grosso, among others. The research focused on the historical circumstances of creation and development of the Evangelical Mission Caiua; therefore, it was given priority as historic sources, documents and interviews with the Guarani-Kaiowá. The Evangelical Mission Caiua in conformity with the patterns of education and evangelization was used by Protestant missionaries as a proposal of civilization and, in some cases, turning the indigenous into laborers, followers of Protestantism and Protestant pastors.
Keywords: Educação - história; Protestantismo; Indígenas; Protestantism; History of education; Indigenous; CIENCIAS HUMANAS::EDUCACAO